T cell receptor usage and epitope specificity amongst CD8+ and CD4+ SARS-CoV-2-specific T cells - Fahnøe, Ulrik; Feng, Shan; Underwood, Alexander P.; Jacobsen, Kivin; Ameri, Amir; Blicher, Thomas H.; Sølund, Christina S.; Rosenberg, Brad R.; Brix, Liselotte; Weis, Nina; Bukh, Jens (Frontiers in Immunology, 2025)
IntroductionThe coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has highlighted the critical importance of understanding protective long-lasting immune responses. This study investigates the epitope specificity, T cell receptor (TCR) usage, and phenotypic changes in SARS-CoV-2-specfic CD8+ and CD4+ T cells over time in convalescent individuals with COVID-19.MethodsPeripheral blood mononuclear cells (PBMCs) were collected from 28 unvaccinated individuals with primary SARS-CoV-2 infection (6 identified as the D614G variant, clade 20C) and analyzed up to 12 months post-symptom onset. Antigen-specific CD8+ and CD4+ T cells were analyzed using flow cytometry and single-cell RNA sequencing (scRNAseq) using specific dextramer and antibody reagents. TCR clonotypes and activation markers were characterized to explore T cell dynamics.ResultsSARS-CoV-2-specific CD8+ T cells exhibited waning frequencies long-term, transitioning from memory-like to a naïve-like state. scRNAseq revealed specificity against both spike and non-spike antigens with increased CD95 and CD127 expression over time, indicating that naïve-like T cells may represent stem cell memory T cells, which are multipotent and self-renewing, likely important for long-lived immunity. TCR clonal expansion was observed mainly in memory T cells, with overlapping TCR beta chain (TRB)-complementary determining region 3 (CDR3) sequences between participants, suggesting shared public TCR epitope-specific repertoires against SARS-CoV-2. Further, unique spike-specific CD4+ T cells with high CD95 and CD127 expression were identified, which may play a crucial role in long-term protection.DiscussionThis study highlights epitope-specificity heterogeneity, with some immunodominant responses, and suggests a potential role for long-lived SARS-CoV-2-specific T cell immunity. Shared TCR repertoires offers insights into cross-reactive and protective T cell clones, providing valuable information for optimizing vaccine strategies against emerging SARS-CoV-2 variants. The findings underscore the critical role of cellular immunity in long-term protection against SARS-CoV-2 and emphasizes the importance of understanding T cell dynamics.